2007
DOI: 10.1017/cbo9780511510908
|View full text |Cite
|
Sign up to set email alerts
|

Finance Capitalism and Germany's Rise to Industrial Power

Abstract: Based on a wide array of data collected by the author, this book uses clear theoretically motivated economic analysis to explain the structure, performance, and influence of universal banks and securities markets on firms during industrialisation. The German universal banks played a significant but not overwhelming role in the ownership and control of corporate firms. Banks gained access to boards via a confluence of their underwriting and brokerage activities, the legal phenomena of bearer shares and deposite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
49
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 146 publications
(54 citation statements)
references
References 199 publications
4
49
0
Order By: Relevance
“…At the time, Metzler (1911) and Riesser (1910) conjectured that the rising taxes fostered concentration in the universal banking industry and moved securities business into the banks and out of the market. Recent work finds some evidence in favor of this idea but not to the extreme described in the contemporary literature (see the lengthy discussion in Fohlin 2002 and2007). 41 To be more precise, the LOT measure declines between each of our measurement years for all but the top quartile of firms.…”
Section: Relation To Earlier Work On Historical Securities Marketsmentioning
confidence: 75%
See 1 more Smart Citation
“…At the time, Metzler (1911) and Riesser (1910) conjectured that the rising taxes fostered concentration in the universal banking industry and moved securities business into the banks and out of the market. Recent work finds some evidence in favor of this idea but not to the extreme described in the contemporary literature (see the lengthy discussion in Fohlin 2002 and2007). 41 To be more precise, the LOT measure declines between each of our measurement years for all but the top quartile of firms.…”
Section: Relation To Earlier Work On Historical Securities Marketsmentioning
confidence: 75%
“…Fohlin (2002Fohlin ( , 2007 hypothesizes that this scholarly neglect may reflect the general (modern) view that these early markets must have been highly inefficient and relatively unimportant within the universal banking system that dominated both academic and public discourse in the post-WWII era.…”
Section: Relation To Earlier Work On Historical Securities Marketsmentioning
confidence: 99%
“…Interlocking directorates, close relationships between banks and industry, and, last but not least, cartels were coordination mechanisms well established in Germany at the turn of the 20 th century. Whereas the relevance of interlocking directorates and of close bank-industry relationships has been intensively investigated (Fohlin, 2007, reviews the literature), the economic impact of cartels has not been fully identified.…”
mentioning
confidence: 99%
“…| 9 relationship of industry and banks (Wellhöner 1989;Fohlin 1999Fohlin , 2002Fohlin , 2007Franks et al 2006;Reckendrees 2013b). It can be debated whether this type of financing industry and the resulting interlocking directorates are more or less efficient then capital markets, 8 but it does not indicate rent-creation.…”
mentioning
confidence: 99%